Loop-mediated isothermal amplification-microfluidic chip for the detection of Trichophyton infection - Jiang, Weiwei; Hu, Dongying; Xu, Yanyan; Chen, Yang; Zhu, Xiaoyang; Han, Zhao; Ye, Xin; Li, Xiaojing (Frontiers in Microbiology, 2022)
Trichophyton is the most pathogenic type of fungal skin infection. It often invades and grows in a keratin-rich matrix, and lesions include human skin, hair, and fingernails (toenails). We designed the LAMP primers of Trichophyton, and developed the LAMP- Microfluidic chip detection system of Trichophyton for the first time. It can detect 6 common species of Trichophyton in the genus Trichophyton, including Trichophyton rubrum, Trichophyton mentagrophyte, Trichophyton violaceum, Trichophyton tonsurans, Trichophyton verrucosum and Trichophyton schoenleinii. The sensitivity can reach 100%, and the sensitivity can reach about 1×102 copies/μL. The entire detection process can be completed quickly within 60 minutes and does not cross-react with other Trichophyton species. The established LAMP- Microfluidic chip detection system has the advantages of simple operation, high specificity and high sensitivity, and has potential for clinical application.